1982
DOI: 10.1515/jpme.1982.10.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Antepartal analysis of fetal heart rate variability by abdominal electrocardiography

Abstract: Antepartal analysis of fetal heart rate variability (FHRV) has been shown to be of value in predicting fetal distress in labor [8]. Abdominal fetal electrocardiograin (aFECG) is used äs a trigger signal in the statistical analysis of intervals and the differences between them [7]. The indices of variability thus obtained have a good correlation with indices calculated simultaneously from direct FECG [6,12]. Interval index (II) describes the long-term variability and differential index (DI) the short-term varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Using spectral analysis, it was demonstrated that a major part of HRV is caused by lowfrequency oscillators, whereas respiratory HRV is much lower in neonates than in adults [14][15][16]. Spectral estimates of the fetal HRV also show maximal power at the lower frequency bands [2,17,18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using spectral analysis, it was demonstrated that a major part of HRV is caused by lowfrequency oscillators, whereas respiratory HRV is much lower in neonates than in adults [14][15][16]. Spectral estimates of the fetal HRV also show maximal power at the lower frequency bands [2,17,18].…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of FHR variability and its significance in fetal well-being have re ceived increased attention in recent years [1][2][3]. Variations in heart rate are attributed to modulation of the depolarization rate of the sino-atrial node through a number of physiological mechanisms such as blood pressure control, thermoregulation or respi ration [4][5][6].…”
mentioning
confidence: 99%
“…[6] suggested that an epoch length of at least five minutes was necessary to obtain good estimates of short-term variability indices. However, KARINIEMI et al found a good correlation between one-minute and five-minute epochs for estimation of DI [18]. Long epochs are advantageous only if the indices can be assumed to be stationary throughout the epoch.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported reference values for NHRV after normal labor and after elective cesarean section [7]. We have also shown previously that rejection logic limits have a considerable effect on the values of variability indices, albeit they are necessary in the quantitative analysis of a noisy signal as from an abdominal fetal electrocardiogram [6]. When reproducing the recorded neonatal electrocardiograms from magnetic tapes, we observed that, in addition to the infant's movements and crying, there are two further principal sources of error in neonatal heart rate tracings: the remote shadow trace caused by premature beats ( Fig.…”
Section: Introductionmentioning
confidence: 93%